Healing the Spirit: William Blake and Magnetic Religion - Rix, Robert (Romanticism on the Net)

(untitled) (Université de Montréal, 2002)
AbstractIn the late eighteenth century, Swedenborg-inspired mystics transformed the pseudo-science of Animal Magnetism, popularized by Franz Anton Mesmer, into a mystical religion of restoring mankind to spiritual health and preparing the Millennium. The essay progresses chronologically to trace Blake's intellectual companionship with this renegade branch of Magnetism in relation to the development of some central metaphors and narrative structures in his works. Especially prominent with the Swedenborgian magnetizers practicing in London were ideas of "healing" by means of communication with spirits from beyond. This, however, met staunch opposition from the Swedenborgian New Jerusalem Church—the only religious organization with which we know Blake to have been affiliated. The more conservative clerics here launched a campaign banishing all experimentation with Spiritualism and the occult interpretations of Swedenborg that held sway among the mystical magnetizers. The article examines Blake's well-known support of Spiritualism in relation to this local dispute, as this contributes to solve the long-standing mystery of why Blake suddenly fell out with New Jerusalem Church at this time and launched a virulent attack on Swedenborg in The Marriage of Heaven and Hell.